Bifid Tongue and Cleft Palate: A Rare Congenital Malformation - Purwanthi, I Gusti Ayu Putri; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; I Made Suka Adnyana; Gede Wara Samsarga; Nyoman Siska Ananda (Jurnal Plastik Rekonstruksi, 2021)
Background: Congenital bifid tongue without other craniofacial abnormalities is a very rare malformation. Here, we discuss a case of the bifid tongue with cleft palate, reported in a 7-month-old girl with no other syndromes or craniofacial abnormalities. Case Reports: This case report described a 7-month-old girl with an anterior bifid tongue, separated medially by a soft, solitary sublingual mass measuring 3 cm x 2 cm in size. There was also an associated incomplete cleft palate. A soft solitary mass measuring 2 cm x 2 cm in size was also seen within the cleft palate. Results: Computed facial tomography (CT) revealed a midline hard palate defect with an intact alveolar process of the maxilla. Pedunculated cystic lesion suspected with epulis was noted to arise on premaxillary alveolar mucosa. Excision of the tongue and hard palate mass and repair of the bifid tongue were done. Summary: Congenital bifid tongue with a cleft is a very rare malformation with different variations. Early surgical intervention is critical to prevent speech impairment and swallowing disorders. A multidisciplinary approach, including well-planned staged operations and rehabilitation, is important to achieve favorable outcomes.